2011
DOI: 10.1097/ta.0b013e3181e50a3b
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide-Releasing Molecule-2 Enhances Coagulation and Diminishes Fibrinolytic Vulnerability in Diluted Plasma In Vitro

Abstract: CORM-2 exposure attenuated the decrease in coagulation kinetics and enhancement of fibrinolytic vulnerability associated with hemodilution. Extensive preclinical investigation remains to be performed to determine the route of administration, safety, and efficacy of CORM-2 and other CORMs to treat trauma-associated bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…were exposed to CORM-2 [51][52][53][54][55][56][57] In order to further characterize the mechanism by which CO enhanced coagulation, experiments involving isolated exposure of prothrombin [58] or fibrinogen [59] to CORM-2 were performed, with the purified protein function assessed in prothrombin or fibrinogen deficient plasmas, respectively. These works lead to the determination that only fibrinogen was affected by CO [58,59], and additional work utilizing mass spectrometry [60] demonstrated that protease digestion of fibrinogen was modified by exposure to CO. More importantly, it was noted that a heme group(s) was present in the fibrinogen digest samples, and following exposure of human plasma to compounds that either produced a carboxyheme or metheme state, plasma strength was increased or decreased respectively, indicative of heme-based modulation of fibrinogen function [60].…”
Section: In Vitro and Preclinical Evidence That Co Is A Procoagulant mentioning
confidence: 99%
See 2 more Smart Citations
“…were exposed to CORM-2 [51][52][53][54][55][56][57] In order to further characterize the mechanism by which CO enhanced coagulation, experiments involving isolated exposure of prothrombin [58] or fibrinogen [59] to CORM-2 were performed, with the purified protein function assessed in prothrombin or fibrinogen deficient plasmas, respectively. These works lead to the determination that only fibrinogen was affected by CO [58,59], and additional work utilizing mass spectrometry [60] demonstrated that protease digestion of fibrinogen was modified by exposure to CO. More importantly, it was noted that a heme group(s) was present in the fibrinogen digest samples, and following exposure of human plasma to compounds that either produced a carboxyheme or metheme state, plasma strength was increased or decreased respectively, indicative of heme-based modulation of fibrinogen function [60].…”
Section: In Vitro and Preclinical Evidence That Co Is A Procoagulant mentioning
confidence: 99%
“…4), with methods used to generate these images as previously cited [84][85][86]. Considered together, these investigations involved conditions or disease states wherein increased CO would be expected to be present, resulting in thrombus ultrastructure (e.g., finer or matted fibers) consistent with enhanced clot strength demonstrated in vitro [48,[51][52][53][54][55][56][57]67,68,[70][71][72][73][74][75][76] or in vivo [68,69] following CO exposure.…”
Section: Ultrastructural Findings Supporting a Procoagulant Role For Comentioning
confidence: 99%
See 1 more Smart Citation
“…Concordantly, electron microscopy revealed that thin, strong fibrin fibers (which are also more resistant to fibrinolysis) form to a greater extent in plasma thrombi than thick, weaker fibers in the presence of CORM-2 [14]. Studies with hemophiliac plasma [15], plasma obtained from subjects administered warfarin [16], and plasma diluted with crystalloid or colloid [17] demonstrated improved coagulation kinetics and decreased vulnerability to lysis following exposure to CORM-2. In sum, rather than increase thrombin generation, CORM-2 modifies the substrate characteristics of fibrinogen, thus enhancing coagulation and attenuating fibrinolysis.…”
Section: Introductionmentioning
confidence: 81%
“…The following variables were determined at 37 C depending on whether or not tPA was present in the reaction mixture: clot growth time (CGT, time from clot amplitude of 2 mm [102 dynes/cm 2 ] until maximum strength is achieved, in s), clot lysis time (CLT, time from when maximum strength was observed to 2 mm amplitude, in s), and clot lifespan (CLS, the sum of CGT and CLT). Additional elastic modulus-based parameters previously described were determined [4,11,13,16,17] and are displayed in Fig. 1.…”
Section: Thrombelastographic Analysesmentioning
confidence: 99%